2021
DOI: 10.1097/nna.0000000000001052
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Intent to Leave their Position and the Profession During the COVID-19 Pandemic

Abstract: The aim of this study was to describe the relationships between perceptions of the pandemic impact on clinical nurses' and nurse leaders' intent to leave their current position and the profession and the differences in pandemic impact and intent to leave variables based on background factors. BACKGROUND: There is much discussion and concern about the COVID-19 pandemic impact on nurses' health and the nursing workforce. METHODS: More than 5000 nurses from a national sample participated in a cross-sectional, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 12 publications
6
94
2
Order By: Relevance
“…Prior to the pandemic, nursing turnover rates were approximately 8% and theses are expected to climb post-pandemic ( Nashwan et al, 2021 ; Raso, Fitzpatrick, Masick, 2021; Sheppard et al, 2021). Raso et al (2021) estimated post-pandemic turnover rates to reach 10%, whereas Sheppard et al (2021) estimated 13% or higher; 22.4% of the CCNs in our study indicated their intent to turnover. Given the relatively small sample size and self-report nature of the study, there are limits to the generalizability of study findings.…”
Section: Discussioncontrasting
confidence: 70%
“…Prior to the pandemic, nursing turnover rates were approximately 8% and theses are expected to climb post-pandemic ( Nashwan et al, 2021 ; Raso, Fitzpatrick, Masick, 2021; Sheppard et al, 2021). Raso et al (2021) estimated post-pandemic turnover rates to reach 10%, whereas Sheppard et al (2021) estimated 13% or higher; 22.4% of the CCNs in our study indicated their intent to turnover. Given the relatively small sample size and self-report nature of the study, there are limits to the generalizability of study findings.…”
Section: Discussioncontrasting
confidence: 70%
“…The study was conducted early in the pandemic. Today, we know the nursing workforce is in crisis with nurses leaving jobs and the profession at high rates ( Raso et al, 2021 ). We might find comments more reflective of this professional discontent if we conducted the interviews now 24 months into the pandemic.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…It is also limited by the location, time, and context in which the interviews were conducted. This study took place in the unique context of the COVID-19 pandemic which undoubtedly increased the workplace stress on the staff during this time ( 40 , 41 ). However, this context may have allowed the nuances of workplace well-being to be further illuminated and thus brought forward in our results.…”
Section: Limitationsmentioning
confidence: 99%